Evaluación de dos biofertilizantes con dos dosis para la producción de forraje verde hidropónico en cebada (Hordeum vulgare)” En La Provincia De Pichincha, Guamaní – 2021 Toaquiza Ugsha Marcia Patricia (2021); Evaluación de dos biofertilizantes con dos dosis para la producción de forraje verde hidropónico en cebada (Hordeum vulgare)” En La Provincia De Pichincha, Guamaní – 2021 - Toaquiza Ugsha, Marcia Patricia (2021)
The research was carried out in the province of Pichincha, Canton Quito, Guamaní Parish, with the objective of evaluating the production of hydroponic green forage in barley (Hordeum vulgare) using two organic biofertilizers Te of manure and liquid Bocashi in two concentrations of 4 - 5%. A completely randomized block experimental design was used with a factorial arrangement (2*2+1) with 6 replications giving a total of 30 experimental units. Five beds were prepared with dimensions of (1.60m L*0.70cm W*0.23cm H). Each bed corresponds to a treatment (4-5% manure tea, 4-5% liquid Bocashi and the control, which corresponds to a chemical nutrient solution). The variables evaluated were: MV, DM (gr), plant height (cm), DR (gr/ml), pH, EC (ppm), bromatological analysis and production cost per treatment. The data were taken periodically. For the MV and DM content, two cutting stages were carried out, the first at 8 days and the second at 15 days, the results obtained were as follows: T2 containing 4% manure tea presented the highest value of MV gain with 2231.77gr and DM with 302.06gr and the lowest behavior presented in terms of MV and DM gain was T5 which corresponds to the FQ Witness with values of 2110.1 and 253.76gr respectively. Regarding the average plant height, data collection was carried out weekly and the results were as follows: T2, which corresponds to the 4% manure tea, presented the highest average plant height with a value of 14.01 cm and T5, which presented the lowest plant height, corresponds to the Witness with a value of 13.94 cm. As for the RD variable, the data were taken by the volumetric method, T4 containing 4% liquid bocashi presented a higher RD with a value of 1.24 gr/ml and T5 which presented the lowest value in terms of RD gain was the treatment containing Witness FQ with a value of 0.90 gr/ml. The EC and pH variable began with a value of 6.45 to 6.30 pH and EC 1400 to 1610, and at the end of the trial this value rose to 7 to 7.6 pH and EC from 1550 to 2000. As for the bromatological analysis variable, the best treatments were 4% manure tea, 5% liquid bocashi and the FQ witness. The results showed the same gain in protein and fiber with values in T2 based on 4% manure tea with protein values of 14.7 and fiber of 27.18%, T3 based on 4% bokashi with protein values of 14.7 and fiber of 27.18%. T3 based on 5% liquid bokashi with values obtained in protein 15.7 and fiber with a higher value of 26.65, and the chemical fertilizer with values obtained in protein 16.37 and fiber with a higher value of 27.28. As for the variable of production cost for 1kg of forage for each treatment for organic production presented a lower value T4 and T3 liquid bocashi with values of $1.61 - $1.63, the T2 - T1 Te of manure presented with values of $1.76 -1.79 and the one that represented the highest value is the Witness with a value of $2.78. It should be emphasized that for the farmer at the moment of implementing the trial, the costs will be significantlyreduced.